Republic of Moldova : Staff Report for the 2006 Article IV Consultation and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses the 2006 Article IV Consultation for Moldova and Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. The economic growth of Moldova has continued to be robust, although the drivers of growth-household consumption and construction-remain heavily dependent on inflows of remittances, as well as strong wage growth. Real GDP growth in 2005 was more than 7 percent, as it has been since early in the decade. Inflation has gradually abated. The trade balance deteriorated significantly in 2005, owing in large part to the impact of higher energy prices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet